-6+4(-5+4n)=11+n

Simple and best practice solution for -6+4(-5+4n)=11+n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+4(-5+4n)=11+n equation:


Simplifying
-6 + 4(-5 + 4n) = 11 + n
-6 + (-5 * 4 + 4n * 4) = 11 + n
-6 + (-20 + 16n) = 11 + n

Combine like terms: -6 + -20 = -26
-26 + 16n = 11 + n

Solving
-26 + 16n = 11 + n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1n' to each side of the equation.
-26 + 16n + -1n = 11 + n + -1n

Combine like terms: 16n + -1n = 15n
-26 + 15n = 11 + n + -1n

Combine like terms: n + -1n = 0
-26 + 15n = 11 + 0
-26 + 15n = 11

Add '26' to each side of the equation.
-26 + 26 + 15n = 11 + 26

Combine like terms: -26 + 26 = 0
0 + 15n = 11 + 26
15n = 11 + 26

Combine like terms: 11 + 26 = 37
15n = 37

Divide each side by '15'.
n = 2.466666667

Simplifying
n = 2.466666667

See similar equations:

| 2w-3w=8w | | 1/4y=7/8 | | 12x+18=11x-7 | | 17/18x73 | | 5x+6-11=4x+3 | | 4/3(3.14)(9)E3 | | -6x-4(-6x-3)=257 | | 260-2/3 | | 4x-1=120 | | 6x+4-2x=16 | | -4(5-w)-(4w-8)=-12 | | -4(5-6)-(4w-8)=-12 | | -8+4v=12 | | 4/3(3.14)(3)E3 | | 8(x-2)=4y | | 4x+20=7x-25 | | -2(p-2)=-2(1-2p) | | -14-z/9=-12 | | 2(10+x)=90 | | 31=6+12+c | | 10x+1-2x=3+8x-10 | | -11=-5(3k+8)+8(-5-k) | | 4(2x-3)=x+9 | | -6(-6n+7)-7=-157 | | 12x-1=-7 | | 3-4(x-3)=3(x-6)-7x | | -21w+5+4w-1= | | 6(-4-x)=-18x | | 0.4x+3=-0.2x-0.6 | | 5x+5=3x+4+2x+1 | | x^2+bx+6.25=0 | | 90=2x+10 |

Equations solver categories